Malaysia, Southeast Asia, and the emerging China political, economic, and cultural perspectives - He, Guozhong 1963-; Yeoh, Kok Kheng (Institute of China Studies, University of Malaya, 2005)
This volume consists of 12 chapters that aim to provide a deeper understanding of the implications of China's emerging influence on the world stage to Southeast Asia, and in particular Malaysia, from various perspectives ranging from the political, economic to the cultural.